Analysis of Work Accident Risk Factors Among Freight Transportation Employees in A Preventive Maqasid Sharia Approach - Nasution, Dhea Anggraini; Irwansyah, Irwansyah (Journal of Public Representative and Society Provision, 2024)
Workplace accidents are a serious issue in the freight transportation sector, causing losses for both employees and companies. This study analyzes risk factors such as age, tenure, and work behavior, while exploring an Islamic approach based on maqasid sharia to minimize accidents. Through a survey of 70 employees at PT Sinar Multi, the results indicate that unsafe behavior is the primary cause of accidents. The Islamic approach, through values such as the protection of life (al-nafs) and trustworthy work, is recommended to enhance safety awareness. This study proposes safety training based on spiritual values as part of a holistic solution.